A perspective of automated programming error feedback approaches in problem solving exercises - Suhailan, S.; Shibghatullah, Abdul Samad; Mohd Aboobaider, Burhanuddin (Little Lion Scientific Islamabad Pakistan, 2014)
Programming tools are meant for student to practice programming. Automated programming error feedback will be provided for students to self-construct the knowledge through their own experience. This paper has clustered current approaches in providing automated error programming feedback to the students during problem solving exercises. These include additional syntax error messages, solution template mismatches, test data comparison, assisted agent report and collaborative comment feedback. The study is conducted based on published papers for last two decades. The trends are analyzed to get the overview of latest research contributions towards eliminating programming difficulties among students. The result shows that future direction of automated programming error feedback approaches may combine agent and collaborative feedback approaches towards more interactive, dynamic, end-user oriented and specific goal oriented. Such future direction may help other researchers fill in the gap on new ways of assisting learners to better understand feedback messages provided by automated assessment tool.